Motorcyclists’ Head Check Behavior During Merging In Traffic: Effect Of Different Ranges Of Merging Lane Length - Abu Hassan, Ahmad Taqiyuddin; Adnan, Ammar; Radin Umar, Radin Zaid; Samuel, Siby; Ani, Mohd Hanafi; Hamid, Malek (Human Factors And Ergonomics Society Malaysia (HFEM), 2017)
Head check is a crucial action to anticipate potential hazards whenever a road user is about to merge onto traffic. Failing to anticipate the hazards may result a road crash. Besides road users’ riding individual behavior, there are several external contributing factors that may influence the head check performances. In this study, the length of the merging lanes of urban expressway was the focus. The objective of the study is to investigate the effect of several ranges of merging lane length on motorcyclists’ head check performance during merging in urban expressways. 1200 motorcyclists were observed at twelve selected scenarios around Klang Valley Metropolitan area (n=100 for each scenario). The twelve scenarios were divided into four categories based on its length – (i) 0-100 feet; (ii) 101-200 feet; (iii) 201-300 feet; and (iv) above 300 feet. Dependent variable for this study was the percentage of head checks. If a motorcyclist turns his or her head over the shoulder towards the target zones (the area in which the potential hazard may emerge – the lanes on the expressway) while in the launch zone (the area that is two seconds before the merging nose), he or she was scored 1, else 0 (i.e. binary scoring). In general, the results show that the percentage of motorcyclists who did not performed head checks (88.17%) is higher compared to motorcyclists who did performed head check (11.83%). Specifically, it was observed that the percentage of head checks among the motorcyclists was higher at the shorter merging lanes rather than the longer merging lanes (i.e. gradually decreases from range (i) to range (iv)). This indicate that the length of merging lanes does affect the head check performance among motorcyclists during merging in urban expressway. The finding may recommend for an improvement to the current riding education curricular. In addition, it also would suggest the optimal range of merging lane length for future merging lane design, in which, may influent head check performance among motorcyclists and reduce the road crashes in the merging areas.